Treatment options for stage IVA thymic malignancies - Girard, Nicolas (Mediastinum; Vol 3 (September 2019): Mediastinum, 2019)
The management of thymic malignancies is based on multidisciplinary collaboration. Stage IVA tumors are defined as tumors associated with intrapleural or intrapericardial dissemination of tumor cells without any distant metastasis. These tumors represent a specific entity with the opportunity of surgical treatment as well as the use of systemic agents if local treatment is not achievable or in combination with surgery, possibly through intrathoracic delivery. Here we describe the available opportunities in such situations, discussing recently available data. Taken together, multidisciplinary tumor board is key for the assessment of patients with stage IVA thymic epithelial tumors (TETs).